1986
DOI: 10.1080/00140138608967258
|View full text |Cite
|
Sign up to set email alerts
|

Air transport pilot involvement in general aviation accidents

Abstract: General aviation (GA) fatal accident records of airport transport pilots (ATPs) were compared to those of private pilots (PVTs). ATPs are safer GA pilots than the PVTs.They have comparable exposure in GA airplanes and account for 7.5% of all certified to fly, but only 3 4 5 % of the fatal accidents. ATPs are less often involved in pilot-induced accidents. Nearly 50% of ATP pilot-induced accidents occur during aerobatics. Often these risky aerial operations are performed below a safe altitude and are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Lower on-airport crash speeds, immediate availability of emergency personnel, and the absence of hazardous terrain all contribute to lower crash fatalities in airport settings (10). Consistent with this study’s finding that aerobatic flight increases the risk of air show–related fatal crashes, aerobatic flights have been described in the literature as the most significant risk factor for fatal injury, comprising 50% of U.S. general aviation crashes involving air transport pilots over a 20-year period (14). In an analysis of the dangers of these maneuvers that used NTSB-reported crash data from 1982 to 2006, de Voogt and van Doom found that more than 80% of the 494 crashes involving aerobatic maneuvers were fatal (15).…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…Lower on-airport crash speeds, immediate availability of emergency personnel, and the absence of hazardous terrain all contribute to lower crash fatalities in airport settings (10). Consistent with this study’s finding that aerobatic flight increases the risk of air show–related fatal crashes, aerobatic flights have been described in the literature as the most significant risk factor for fatal injury, comprising 50% of U.S. general aviation crashes involving air transport pilots over a 20-year period (14). In an analysis of the dangers of these maneuvers that used NTSB-reported crash data from 1982 to 2006, de Voogt and van Doom found that more than 80% of the 494 crashes involving aerobatic maneuvers were fatal (15).…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…This difference could very well contribute to the lower level of aerodynamic stalls as a commercial license requires pilots to maintain control of the aircraft under conditions approaching a stall to a higher standard than aviators tested for the private pilot certificate (US Department of Transportation documents FAA-S-8081-12C and FAA-S8081-14B respectively). Moreover, earlier studies had reported a reduced involvement of ATP pilots in general aviation accidents (Salvatore et al, 1986) as well as fewer pilot errors (Li et al, 2001). On the other hand the logistic regression showed little evidence of a risk reduction for a fatal accident with advanced certification arguing against this possibility at least with respect to twin engine aircraft.…”
Section: Discussionmentioning
confidence: 95%
“…The improper handling of aircraft dynamics, errors in decisionmaking systems, and negligence were the most common causes of pilot errors, which should be focused on the pilot training [4]. Salvatore S found that aviation accidents were most likely to occur in summer and early autumn [5]. Sun Ruishan found that the occurrence time of global aviation accidents was different in different periods.…”
Section: Introductionmentioning
confidence: 99%